Pemberdayaan Masyarakat di Pesisir Pantai Kota Manado Menghadapi Ancaman Bencana Tsunami Guna Mewujudkan Masyarakat Tangguh Bencana - Imansyah, Mulya (PT Hakhara Akademia Indonesia, 2023)
Sario Tumpaan Village is one of the villages in Sario District, Manado City, North Sulawesi Province which is a coastal area that has a high potential threat of tsunami hazard, while in that area there are still physical and environmental vulnerability conditions so that efforts to reduce disaster risk are still questionable. This study aims to analyze the empowerment of coastal communities to face the potential threat of a tsunami, stakeholder involvement, and empowerment efforts to build disaster-resilient communities. This study uses a qualitative approach, with an analytical descriptive design, using primary and secondary data, through interview techniques, observation, and document studies as well as qualitative data analysis using the interactive model of Miles, Huberman, and Saldana. The results of the study found that the empowerment of coastal communities was carried out through enabling activities, namely providing access to the community to participate in the stages of disaster management activities both pre, during, and post-disaster; Empowering, namely after being given access, the community is also given reinforcement in the form of providing facilitators and supporting equipment needed as part of capacity building; and Protecting: namely providing protecting through institutional stipulation, as well as legal aspects through advocacy to related parties. Meanwhile, to see disaster resilience in coastal areas, it is assessed with 5 components and 28 indicators of regional resilience. Overall efforts to empower communities on the coast of Manado City against the potential threat of a tsunami disaster have been going well, but it is hoped that the community can become more independent. Stakeholders involved in efforts to empower coastal communities to include elements of government, community, business, academics, and mass media that work together through programs of training, simulation, socialization, and the establishment of regional disaster risk reduction forums coordinated by BPBD, and efforts to Realizing a disaster-resilient community already exists and continues to be improved through the disaster-resilient Village program through policies, risk studies, planning, institutions, financing, and the involvement of all interested parties. Or keep people away from disasters, keep disasters away from people and live in harmony with disaster risks.